Pengaruh Financial Distress, Pergantian Manajemen, Opini Audit, Koneksi Politik, Financial Restatement Terhadap Auditor Switching - Aurellia Leonanta Dewi; Rina Trisnawati (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2024)
This research aim to analyze the factors that affect auditor switching, namely, financial distress, management changes, audit opinions, political connections, and financial restatement. The object of this research was infrastructure companies listed on the IDX in 2020-2023. This research used quantitative research with logistic regression analysis and data processing with SPSS. The sampling technique used was purposive sampling. The number of samples was 96 companies during 2020-2023. Data obtained from www.idx.co.id. The results of this research state that financial distress, management changes, audit opinions, and political connections don’t have a significant effect on auditor switching. Meanwhile, financial restatement has a significant effect on auditor switching,